Reactivation potency of two novel oximes (K456 and K733) against paraoxon-inhibited acetyl and butyrylcholinesterase: In silico and in vitro models - Iqbal, Amna; Malik, Shahrukh; Nurulain, Syed M; Musilek, Kamil; Kuca, Kamil; Kalasz, Huba; Fatmi, M Qaiser (Chemico-biological interactions, 2019)
Organophosphates (OPs) irreversibly inhibit acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes. The reactivation of these inhibited enzymes is paramount for their normal function. Present study evaluates reactivation potency of two newly developed oximes, K456 and K733, against paraoxon (POX)-inhibited human-RBC-AChE and human-plasma-BChE in comparison to reported reactivator, pralidoxime (2-PAM). In vitro studies showed higher intrinsic toxicities of both oximes than 2-PAM for AChE. No substantial reactivation of hBChE was noted by tested concentration. Contrary to 2-PAM, the in silico study predicted lower binding free energies for both oximes. However, the detailed interaction study revealed inability of oximes to interact with catalytic anionic site of AChE and hBChE in contrast to 2-PAM. Both in vitro and in silico studies conclude that K456 and K733 are unlikely to be used as reactivators of paraoxon-inhibited AChE or BChE.
Keywords: Erythrocytes; Acetylcholinesterase; Butyrylcholinesterase; butyrylcholinesterasa; oximy; Oximes; lidé; Paraoxon; Pyridinium Compounds; cholinesterasové inhibitory; paraoxon; reaktivátory cholinesterasy; Cholinesterase Inhibitors; pyridinové sloučeniny; erytrocyty; Humans; acetylcholinesterasa; Cholinesterase Reactivators